The Anticancer Potency of Pandanus odoratissimus Extracts In Human Breast Cancer (MCF-7) Cell Line - Andriani, Yosie; Yahya, Rodhiyah; Gazali, Mohamad; Amir, Hermansyah; Subhan, Beginer (Jurnal Laot Ilmu Kelautan, 2024)
The development of novel chemical entities, novel pharmaceuticals, and novel drug leads frequently involves the use of natural sources. One of the most well-known plants, Pandanus odoratissimus (Pandanaceae), is native to Malaysia and has long been used in Ayurvedic medicine to treat a variety of illnesses. The purpose of this study is to determine P odoratissimus's antioxidant and anticancer properties against MCF-7 human breast cancer cell lines. The 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity was used to assess antioxidant activity, and among the other extracts, core exhibited the highest antioxidant value. An MTT assay was used to assess the effects of plant components on MCF-7 cell lines (3-(4, 5-dimethylthiazolyl)-2, 5-diphenyl-tetrazolium bromide). The concentration of samples was shown to considerably boost the antioxidant activities in P. odoratissimus extracts. Our findings demonstrated that, after receiving treatment for 72 hours, sample treated cancer cells experienced a decline in cell viability. The IC50 value of 88.00 mg/ml indicates that the extracts have a poor cytotoxic impact and have no promise as anticancer agents against MCF-7, which is why it’s killing efficiency in cancer cells is regarded as lower.